Study of the Length Frequency Distribution of Sucker Head, Garra gotyla gotyla (Gray, 1830) in Different Rivers and Seasons in Nepal and Its Applications - Jha, Bibhuti Ranjan; Waidbacher, Herwig; Subodh, Sharma; Straif, Michael (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Size structure data particularly that of length frequency distribution is very important fisheries management tool. This is also applied to assess the health, habitat and integrity of the rivers. Nepal is tremendously rich in both fisheries and water resource and thus, this analysis is very important. However, this kind of analysis is not common in fisheries studies and hence the size structure information of all the fish in Nepal is wanting. This study simply tries to open the door for such studies with the study of the sucker head Garra gotyla gotyla, a very common fish in Nepal. The field observation was done in nine rivers of the country in all the seasons of the 2003 by using electrofishing gear. The length frequency distribution of the river was found to vary both spatially and temporally among rivers and seasons respectively indicating different conditions in different rivers. The study suggested that the beginning of the breeding season should be immediately before monsoon. The rivers Aandhikhola and Tinau were found to possess some of the best distributions of length frequencies of this species and hence have a better habitat conditions and water quality.